Action-Based Learning in Environmental Education for Elementary School Students Through Ecotourism - Annas, Faris Budiman; Lubis, Djuara P.; Hapsari, Dwi Retno; Sumardjo, Sumardjo (Proceedings Series on Social Sciences & Humanities, 2025)
This study explores the implementation and impact of action-based learning in environmental education for elementary school students through ecotourism, using Organic Agro-Edu Tourism (AEWO) Mulyaharja in Bogor, Indonesia as a case study. Employing a qualitative research approach, data were collected through interviews, focus group discussions, observations, and document analysis involving students, teachers, local residents, and AEWO staff. The findings reveal that AEWO provides meaningful, hands-on learning experiences in organic agriculture, fostering emotional and cognitive connections to nature. Students gain not only agricultural knowledge but also develop greater empathy, responsibility, and appreciation for environmental sustainability. The integration of local farmers in the learning process enhances the authenticity and relevance of education, while the ecotourism setting enables place-based learning that extends beyond classroom boundaries. This research concludes that action-based learning within ecotourism frameworks significantly contributes to raising environmental awareness and shaping pro-environmental behavior among young learners.